Artificial Intelligence and the Future of Digital Marketing - Juriah, Siti; Susilastuty, Darwati (Green Publisher Indonesia, 2024)
This research aims to explore the use of artificial intelligence (AI) in digital marketing among MSME practitioners in Indonesia. In an increasingly evolving digital era, understanding and implementing AI technology becomes crucial for MSMEs to improve their competitiveness and marketing effectiveness. This study involved 50 respondents who are MSME actors and used a quantitative method with questionnaires to collect data. The results indicate that 72% of respondents have a basic understanding of AI; however, only 44% have implemented AI-based tools in their marketing strategies. Furthermore, linear regression analysis revealed a significant relationship between the use of AI and increased sales, with a regression coefficient of 0.75 (p < 0.01), demonstrating that the use of AI positively contributes to marketing outcomes. The study also found that the use of AI tools such as chatbots and automated copywriting can enhance customer engagement. Although MSME actors show awareness of AI's potential, there exists a gap between knowledge and practice. Therefore, this research recommends the need for greater training and support for MSMEs to maximize the use of AI in their digital marketing strategies. The findings are expected to provide insights for stakeholders and policymakers in designing initiatives that support the integration of AI technology in MSME businesses, allowing them to adapt to changes and improve marketing effectiveness.